PENGARUH KOMPRES HANGAT TERHADAP PENURUNAN SKALA NYERI PADA PASIEN DENGAN KOLIK ABDOMEN DI RUANG RAWAT INAP RUMAH SAKIT LAWANG MEDIKA - Qurrata Ayun, Sofa; Retno Wati, Dwi; Ratna Aminati, Fifi (LPPM STIKES HUSADA JOMBANG, 2022)
Blood thinning or hemodilution in pregnant women, there is an increase in blood plasma volume of 30%-40%, an increase in red blood cells 18%-30% and hemoglobin 19%. Physiologically hemodilution to help ease the work of the heart. Hemodilution occurs as early as 10 weeks' gestation and reaches its peak at 32-36 weeks' gestation. If the hemoglobin is before about 11%, hemodilution will result in physiological anemia and the hemoglobin will drop to 9.5-10%. This study aims to determine the effect of guava juice on changes in hemoglobin levels of pregnant women in the third trimester at Pratama Rahma Clinic. The research design used was Quasi Experiment using Pre Post Test control Group Design. The sampling method in this study used purposive sampling with a total sample of 30 pregnant women, namely 15 pregnant women in the control group and 15 pregnant women in the intervention group. Hemoglobin measurement tool using Easy Touch Blood Hemoglobin. Bivariate analysis in this study used paired t-test and independent t-test. The results showed that the combination of guava Fe was more effective in increasing the hemoglobin level of pregnant women, which was indicated by the p- value = 0.001 < (0.05). Pregnant women can use guava juice in combination with Fe tablets as an alternative choice in increasing hemoglobin levels during pregnancy.